Efficacy of different routes of triamcinolone acetonide administration on macular edema: A systematic review and network meta-analysis. - Kexin Liu; Jinyang Yi; Juan Xu; Li Zhong; Na Su (PLoS ONE)
There is different administration routes of triamcinolone acetonide (TA) administration for macular edema, but the efficacy ranking remains unclear. The purpose of this study is to assess the efficacy of different administration routes of TA employed in macular edema. PubMed, Medline, Embase, and Cochrane Central Register of Controlled Trials were systematically searched for published articles comparing macular edema in patients with triamcinolone acetonide in different administration. The sparse network was evaluated using a random-effects model and consistency model within the Bayesian framework, utilizing the multinma package in R. The evidence was assessed based on the Grading of Recommendations. Assessment, Development, and Evaluation (GRADE) criteria. A total of 1138 citations were identified by our search, of which 20 RCTs enrolled 892 eyes. The network showed that intravitreal triamcinolone acetonide (IVTA) was associated with a statistically significant better best corrected visual acuity (BCVA) at the 12th week compared to placebo (MD: - 0.15, 95% CI: - 0.30 to - 0.01, P < 0.05), which was moderate-quality evidence. IVTA and suprachoroidal triamcinolone acetonide (SCTA) were both associated with a statistically significant reduction in central macular thickness (CMT) at the 12th week, which was moderate evidence. The probabilities of rankings and SUCRA demonstrated that sub-Tenon's infusion of triamcinolone acetonide (STiTA) might be the worst. SCTA and IVTA were proven to be the best administration routes for improving BCVA and reducing CMT. In addition, STiTA was less advisable than other administration routes of triamcinolone acetonide according to the rankings and SUCRA.